Caregiver Engagement in Stroke Care: Opportunities and Challenges in Australia and Denmark - Lobo, Elton H.; Abdelrazek, Mohamed; Grundy, John; Kensing, Finn; Livingston, Patricia M.; Rasmussen, Lene J.; Islam, Sheikh Mohammed Shariful; Frølich, Anne (Frontiers in Public Health, 2021)
Globally, there is a rise in incident cases of stroke, particularly in low- and middle-income countries, due to obesity-related and lifestyle risk factors, including health issues such as high cholesterol, diabetes and hypertension. Since the early 20th century, stroke mortality has declined due to proper management of the risk factors and improved treatment practices. However, despite the decline in mortality, there is an increase in the levels of disability that requires long-term support. In countries such as Australia and Denmark, where most care is provided within the community; family members, generally spouses, assume the role of caregiver, with little to no preparation that affects the quality of care provided to the person living with stroke. While past research has highlighted aspects to improve caregiver preparedness of stroke and its impact on care; health planning, recovery, and public health policies rarely consider these factors, reducing engagement and increasing uncertainty. Hence, there is a need to focus on improving strategies during recovery to promote caregiver engagement. In this study, we, therefore, try to understand the needs of the caregiver in stroke that limit engagement, and processes employed in countries such as Australia and Denmark to provide care for the person with stroke. Based on our understanding of these factors, we highlight the potential opportunities and challenges to promote caregiving engagement in these countries.